Water Safety Workshop for First Aid Supplies for Swimming Pool Accidents - Zakaria Wahyu Hidayat; Aditya Harja Nenggar; Faisol Hamid; Mohammad Zaim Zen; Yully Wahyu Sulistyo (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Abstract: Water Rescue is a series of steps to help rescuers remember how to deal with water accidents. This method is often also known as the RTRGT method, which stands for Reach, Throw, Row, Go, and Tow. This method has been proven and is the most effective rescue method in providing assistance to victims who are threatened with drowning. Disasters or emergencies are events that are always unexpected by anyone, including rescuers / SAR teams. It requires a response or handling as soon as possible without forgetting the safety factor (self-safety). Therefore, basic water rescue abilities and skills should not only be possessed by those who work as SAR teams but everyone so that in the event of an emergency, the number of victims can be minimized. Good and correct rescue techniquesnot only make it easier for rescuers to carry out rescues but can also guarantee the safety of the rescuer himself. Many cases occur where the safety of the rescuer is threatened due to limited knowledge. Not infrequently, the rescuer has to lose his life because he was reckless in carrying out rescue actions only with the capital of swimming skills. Swimming ability is the main and most important capital in water rescue, but it must be noted that water rescue does not always require the rescuer to